2006
DOI: 10.1002/ajmg.a.31372
|View full text |Cite
|
Sign up to set email alerts
|

A novel mutation in GDF5 causes autosomal dominant symphalangism in two Chinese families

Abstract: Proximal symphalangism (SYM1) is an autosomal dominant disorder characterized by ankylosis of the proximal interphalangeal joints and fusion of carpal and tarsal bones. We identified and characterized two five-generation Chinese families with SYM1. The two families share some similarities (e.g., osseous fusion of interphalangeal joints of the 2-4 fingers) with SYM1 families with mutations in the NOG gene or the family with mutation R438L recently reported in the GDF5 gene (encoding a bone morphogenetic protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 22 publications
1
31
0
Order By: Relevance
“…Interaction analyses of GDF5 W414R using chondrogenic differentiation assays together with Biacore binding studies revealed a NOG resistance as molecular cause of the joint fusion phenotype similar to GDF5 N445T and GDF5 S475N [15], [17]. In addition, we identified NOG insensitivity as the effect of the SYM1 associated GDF5 E491K mutation [14]. Hence, in case of SYM1 and SYNS2, an impaired GDF5/NOG interaction interferes with the negative feedback loop by which GDF5 is antagonized and thus balanced within the fine-tuned signaling network.…”
Section: Discussionmentioning
confidence: 68%
“…Interaction analyses of GDF5 W414R using chondrogenic differentiation assays together with Biacore binding studies revealed a NOG resistance as molecular cause of the joint fusion phenotype similar to GDF5 N445T and GDF5 S475N [15], [17]. In addition, we identified NOG insensitivity as the effect of the SYM1 associated GDF5 E491K mutation [14]. Hence, in case of SYM1 and SYNS2, an impaired GDF5/NOG interaction interferes with the negative feedback loop by which GDF5 is antagonized and thus balanced within the fine-tuned signaling network.…”
Section: Discussionmentioning
confidence: 68%
“…We detected a highly significant decreased risk in female C-allele carriers, when compared with women with the TT genotype. Since GDF5 mutations are known to cause specific abnormalities in the development of the phalanges in humans,6 7 8 9 10 11 12 13 an association with hand OA is not surprising. Recently, GDF5 was found to be borderline significantly associated with hand OA in a pooled analysis from three cohorts using in total 955 cases and 2742 controls 16.…”
Section: Discussionmentioning
confidence: 99%
“…Both disorders are characterised by shortening of the digits. Activating mutations in GDF5 will lead to symphalangism and several types of acromesomelic chondrodysplasia,7 9 10 11 12 13 all characterised by ankylosis (bony fusion) of joints. Although GDF5 mutations result in many skeletal syndromes, they seem to have in common that limb and, in particular, hand, abnormalities are present.…”
mentioning
confidence: 99%
“…Corroborating this, disruption of the mouse Noggin gene results in enlarged condensations and joint fusions (Brunet et al, 1998). Of interest, a certain subset of mutations in GDF5 were also shown to be associated with joint fusions (Seemann et al, 2005;Dawson et al, 2006;Wang et al, 2006;Yang et al, 2008;). These mutations generally result in an activation of BMP signalling, for example by an increased binding of GDF5 to BMPR1A.…”
Section: Segmentation Of the Digitsmentioning
confidence: 91%